2010
DOI: 10.4067/s0718-686x2010000200007
|View full text |Cite
|
Sign up to set email alerts
|

Poliquetos Bentónicos Intermareales Y Sublitorales De La Región De Aisén, Chile

Abstract: Composition, abundance and richness of the intertidal and shallow subtidal (<30 metres) benthic polychaetes are presented. Several coastal fieldworks in fjords, channels and islands were undertaken between 2001 and 2003 in relationship with Biodiversity Aysen Project. 1.364 individuals and a total number of 76 taxa belonging to 30 families were recorded. The higher species richness was observed by Spionidae and Nereididae with nine and eight species respectively, with Platynereis australis (Schmarda, 1861) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Blake & Kudenov (1978: 238), however, suggested that "his descriptions match those of B. tricuspa (Hartman), and his specimens should probably be referred to the latter species." Soto & Paterson (2010) reported B. proboscidea collected from the Región de Aisén, southern Chile, in 2002. However, we re-identified their specimens as Boccardia claparedei (Kinberg, 1866) based on the photos provided by the authors on our request (Soto in litt., 27 Nov 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Blake & Kudenov (1978: 238), however, suggested that "his descriptions match those of B. tricuspa (Hartman), and his specimens should probably be referred to the latter species." Soto & Paterson (2010) reported B. proboscidea collected from the Región de Aisén, southern Chile, in 2002. However, we re-identified their specimens as Boccardia claparedei (Kinberg, 1866) based on the photos provided by the authors on our request (Soto in litt., 27 Nov 2018).…”
Section: Discussionmentioning
confidence: 99%
“…(in press) have summarized the knowledge of Syllidae in Chile. Moreover, the records of Syllidae in the Patagonian region of Chile (41°–55°S) are mainly related to ecological works indicating the presence of species for different localities such as Aysén fjord, Los Chonos Archipelago, Magellan Strait and Beagle Channel (Cañete et al ., 1999; Gambi & Mariani, 1999; Thatje & Brown, 2009; Soto & Paterson, 2010; Montiel et al ., 2011). Currently, 24 species of syllids have been reported in Chilean Patagonia showing that Syllis is the most diverse genus with eight species (San Martin et al ., in press).…”
Section: Introductionmentioning
confidence: 99%